Analisis Postur Kerja pada Pembuatan Rumah Boneka dengan Metode Rapid Entire Body Assessment - Tiara Mardi; Surya Perdana (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
PT. X is a company engaged in the manufacture of the doll house. Its various daily production processes in each work station are performed on the floor by squatting for long hours. There are seven work stations, namely pattern making, pattern cutting, pattern assembly, caulking, sanding, painting and accessory installation. The study aims to know the risk level of working posture of operators and to suggest improvements to very risky work stations. The method used in this research is Rapid Entire Body Assessment (REBA) based on nordic questionaire on pains suffered in the back, waist, hip, right hand and foot. From the results of the collection and processing of the data, the risk of injury in an actual working system based on REBA score shows a high risk level, with the highest risk level is in caulking working station of 9 for the left side and 8 for the right side. Further, the suggested working system improvement using a chair and table results in a decrease in the risk of injury with low REBA score, the average of which is 5 for all improved work stations. It shows that the suggested working system improvement is really necessary to reduce the work risks during the doll house production.